Resilience Amidst Challenges: Unraveling Factors Shaping Unemployment In Yogyakarta Special Region - Arya Putra, Tatas (Ekonomi dan Bisnis, 2024)
The issue of unemployment in Indonesia, especially in the Special Region of Yogyakarta, has become a matter that requires careful attention. This research investigates the factors influencing the unemployment rate in the region during the period 2015-2022. The independent variables used in this study are capital expenditure, education, poverty, and the Covid-19 pandemic. Data were collected from the Central Statistics Agency (BPS) of the Special Region of Yogyakarta and then analyzed using panel data regression. The panel data model employed was the Fixed Effect Model (FEM). The findings of this study indicate that, individually, capital expenditure, education, and poverty do not have a significant impact on unemployment. From these results, only the Covid-19 variable significantly influences unemployment. Simultaneously, all independent variables (capital expenditure, education, poverty, and Covid-19) collectively have a significant impact on the unemployment variable. The overall independent variables, including capital expenditure, education, poverty, and the Covid-19 pandemic, can explain the fluctuations in the dependent variable by 51.12%, with the remaining variations attributed to other factors outside the model. Based on the outcomes of this research, it is hoped that the government will consider developing targeted skill training programs, collaborating with the private sector to create new job opportunities, and fostering local economic innovation to stimulate growth in sectors with high potential for job creation. Keywords: Capital Expenditure; Education; Poverty; Covid-19; Unemployment